Evaluation of residual stress and distortion distribution using finite element analysis - Hieng, Pheak Kdey (2016)
This study is mainly focused on the estimation of the surface residual stress after the welding on aerospace materials. Finite element analysis using the software, ANSYS, is carried out to evaluate the residual stress distribution and deformation field at the surface level after welding. Two methods of simulations are used to obtain the welding results. One method is to simulate a simple heat source moving across the plate and another method is to simulate the heat source moving with the effect of deposition of filler metal material. The numerical analysis is carried out on two different plates, square and rectangular. The simulation results will be used to compare and correlate with the experimental results that has been performed and given. From the square plate, simulation results done by another software, Salome, are also shown to compare with the simulations in this study. This is used to verify and support that the simulations done are accurate. Overall, this study aims to validate the experimental residual stress by carrying out the welding simulations on two different plates using finite element analysis in ANSYS.